2022
DOI: 10.1002/cfp2.1140
|View full text |Cite
|
Sign up to set email alerts
|

Americans' financial resilience during the pandemic

Abstract: How household wellbeing responds to pandemic-induced financial shocks likely depends on whether people undertake certain actions that enhance their ability to withstand adverse economic events, along with their ability to efficiently respond to the shocks when they occur. This paper examines Americans' financial robustness during the Covid-19 pandemic, using an index of financial resilience and a measure of financial fragility derived from household surveys of persons age 45-75 in spring of 2020, and in May-Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…To that end, Canilang et al (2020) analyzed data from the Survey of Households and Economic Decision Making of July 2020, and they concluded that such relief efforts helped provide a short-term safety net. Moreover, in line with our empirical findings, Clark and Mitchell (2022) found that their financial resilience index remained relatively stable from the beginning of the pandemic in 2020 to a year later in 2021, a result the authors attributed to the government's financial support programs including stimulus payments to low-and moderate-income households as well as higher unemployment benefits. Similar results were found by Asebedo et al (2020) who collected their own data during the onset of the pandemic and reported that the stimulus payments especially helped those with fewer financial resources, higher job insecurity, and more financial constraints through debt repayment.…”
Section: Changes In Reported Debtconstraint Measures Between 2020 And...supporting
confidence: 88%
“…To that end, Canilang et al (2020) analyzed data from the Survey of Households and Economic Decision Making of July 2020, and they concluded that such relief efforts helped provide a short-term safety net. Moreover, in line with our empirical findings, Clark and Mitchell (2022) found that their financial resilience index remained relatively stable from the beginning of the pandemic in 2020 to a year later in 2021, a result the authors attributed to the government's financial support programs including stimulus payments to low-and moderate-income households as well as higher unemployment benefits. Similar results were found by Asebedo et al (2020) who collected their own data during the onset of the pandemic and reported that the stimulus payments especially helped those with fewer financial resources, higher job insecurity, and more financial constraints through debt repayment.…”
Section: Changes In Reported Debtconstraint Measures Between 2020 And...supporting
confidence: 88%
“…For example, Klapper and Lusardi (2020) find that about 55% of people in developed economies know how to handle their own money, but only 28% of adults in major developing economies do. Financially literate consumers have the ability to absorb any financial shock (Clark and Mitchell, 2022). An inevitable overlap in terms of financial literacy and financial capability usage as part of financial inclusion has been observed.…”
Section: Review Of Earlier Studies and Hypotheses Developmentmentioning
confidence: 99%
“…Clark and Mitchell (2022) investigate the impact of Covid-19 on Americans' financial stability and their crisis-management strategies. The Federal Reserve and government's efforts in the form of stimulus packages and direct benefit transfers have significantly contributed to the achievement of financial resilience, which is bolstered by financial literacy.…”
Section: Introductionmentioning
confidence: 99%
“…Financial fragility is used to describe the individuals' and/or households' incapacity to cope with financial shocks and unexpected expenses (Clark & Mitchell, 2022). Ex-amples of such shocks is a decrease in working hours and salaries, job losses, changes in loan interest rates or stock markets and also physical disability, divorce, or death, (Ramli et al, 2022).…”
Section: Introductionmentioning
confidence: 99%